Are there also negative effects of social support? A qualitative study of patients with inflammatory bowel disease - Alexander Palant; Wolfgang Himmel (BMJ Open)
Objective Social support is considered an important resource in coping with chronic conditions. By conducting a series of interviews with people who suffer from inflammatory bowel disease (IBD), we received the impression that social support in face-to-face or online communication could also be a source of stress and strain. The aim of our study was to better understand and describe possible negative effects of social support.Design This is a secondary analysis of narrative interviews. The interviewees were selected using a maximum-variation sampling approach. Grounded theory and the ‘OSOP’ (one sheet of paper) method were applied to categorise those parts of the interviews that touched on the negative effects of social support.Setting The open-end interview collection took place throughout Germany from September 2011 to June 2012. Most of the participants were interviewed in their homes, some in the Department of General Practice in Göttingen.Participants 42 patients with IBD.Results Two interrelated categories emerged: (1) unwanted confrontation and (2) undesirable reactions. The interviewees perceived social support as negative, especially if they felt overwhelmed and/or if they had not asked for it. Consequently, some of our interview partners developed strategies to prevent coming into social contact with others or stopped talking entirely about their disease.Conclusion While social support is usually conceptualised and perceived as a positive resource in chronic disease, it sometimes turns into a negative experience and may end in social isolation and deteriorate health. This process also happens in online support groups and increases anxiety when exchanging with other people on the internet. Before motivating ill people to seek contact with others, they should know about the negative effects of social support.